Analisis Pengendalian Persediaan Bahan Baku Tauco di Perusahaan Kecap Manalagi Kota Denpasar Provinsi Bali - IDA BAGUS MANIK BRAHMANDHIKA; RATNA KOMALA DEWI; I KETUT SUAMBA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Analysis Of Raw Material Inventory Control of Tauco On The KetchupManalagi Company Denpasar BaliThis study was conducted to examine the essential part of a company namely rawmaterial. The purpose of this study was to determine the amount of raw materialinventory control efficiency in implementing the manufacture company's rawmaterial inventory control systems are efficient. The actual raw material controllingon the Kecap Manalagi’s company is 2.500 kg, 23% holding cost, ordering cost perorder is Rp 1.300.000 and the price of tauco is Rp 9.925 per kg. Economic OrderQuantity (EOQ) method that should be done by the company is 7.275 kg, with sixtimes frequency in a year of ordering raw material, and the exact re-order point forcompany is 3.197 kg. The results showed that the total cost of inventory in the EOQmethod of Rp 16.608.313, while the total cost of the actual inventory of Rp27.020.437, so that savings are Rp 10.412.124 (38,5% of the actual total inventorycost). The suggestions that the authors recommend is (1) companies need to reviewthe control methods applied during this time, because it is based on the calculationmethod used by the researchers also companies need to review the ordering costand holding cost so the cost of the inventory can be minimize.